The Journey of Indonesian Government Accounting - Fandi Prasetya (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
From 1974 to today, Indonesia has undergone many periods of financial management reform. Financial management reform is necessary for a country to attain excellent governance. The crisis that happened in 1997 prompted the adoption of good Governance in Indonesia. The 1997 financial crisis revealed the inadequate management of public finances up until that point. Thus, the Indonesian government began to recognize excellent governance gradually. Government Accounting Standards are the first step towards achieving excellent Governance (SAP). In Government Regulation 71 of 2010, Accrual-based SAP is the proper SAP for implementing good governance. Government Regulation No. 71 of 2010 implements Law No. 17 of 2003 About the Financial Country. Using the accrual method is anticipated to enhance the transparency of financial reporting and the government's public accountability. This type of qualitative descriptive research seeks to comprehend how the transition from pre-reform to the post-reform application of Government Accounting Standards happened. Through a literature search, the data for this investigation were acquired